Covalency‐Driven Preservation of Local Charge Densities in a Metal‐to‐Ligand Charge‐Transfer Excited Iron Photosensitizer. Issue 31 (8th July 2019) - Jay, Raphael M.; Eckert, Sebastian; Vaz da Cruz, Vinícius; Fondell, Mattis; Mitzner, Rolf; Föhlisch, Alexander
Abstract: Covalency is found to even out charge separation after photo‐oxidation of the metal center in the metal‐to‐ligand charge‐transfer state of an iron photosensitizer. The σ‐donation ability of the ligands compensates for the loss of iron 3d electronic charge, thereby upholding the initial metal charge density and preserving the local noble‐gas configuration. These findings are enabled through element‐specific and orbital‐selective time‐resolved X‐ray absorption spectroscopy at the iron L‐edge. Thus, valence orbital populations around the central metal are directly accessible. In conjunction with density functional theory we conclude that the picture of a localized charge‐separation is inadequate. However, the unpaired spin density provides a suitable representation of the electron–hole pair associated with the electron‐transfer process. Abstract : Covalent effects compensate for photo‐induced charge variations within a charge‐transfer excited transition‐metal dye. Using time‐resolved X‐ray absorption spectroscopy and DFT calculations, the underlying mechanism is found to uphold local charge densities at the photo‐oxidized transition‐metal center, while transferring spin density to peripheral parts of the molecule.